Analyzing STEAM project-based learning in PAUD Terpadu 'Aisyiyah Nur'aini unit II Yogyakarta - Miftahul Ichlas; Prima Suci Rohmadheny; Dwi Hastuti; Avanti Vera Risti Pramudyani (Journal of Early Childhood Care and Education, 2023)
Project-based learning enables teacher to guide the learning process and development of various developmental aspects of students. One of them is through the STEAM project with three stages: preparation, development, and conclusion. STEAM is a collaborative learning that facilitates motivation and innovation allowing for students’ creativity. Hence, students can strengthen not only their cognitive aspect. Integrated Early Childhood Education (PAUD Terpadu) ‘Aisyiyah Nur’aini Unit Two Yogyakarta is a pilot school that implements STEAM project-based learning. However, no research has discussed the implementation. Therefore, the present study aims to know, analyze, and describe STEAM project-based learning. The research subjects, or the informants, were four classroom teachers for children aged five to six. The classes implement STEAM project-based learning. The research belongs to a case study with the data collected through interviews, observation, and documentation. The data were analyzed using Miles and Huberman techniques with three stages: data collection, data reduction, and conclusion drawing. The results showed several characteristics of STEAM project-based learning in PAUD Terpadu ‘Aisyiyah Nur’aini Unit Two. It emphasizes the students and provides them with critical and creative thinking and problem-solving through the teachers’ roles.